Role of Cytokines in Thymic Regulatory T Cell Generation: Overview and Updates - Tang, Mei; Jia, Fuya; Nan, Fang; Zuo, Fengqiong; Yuan, Zhu; Zhang, Dunfang (Frontiers in Immunology, 2022)
CD4+CD25+Foxp3+ Regulatory (Treg) T cells are mainly generated within the thymus. However, the mechanism of thymic Treg cell (tTreg cell) generation remains to be fully revealed. Although the functions of TCR/CD28 co-stimulation have been widely accepted, the functions of cytokines in the generation of tTreg cells remain highly controversial. In this review, we summarize the existing studies on cytokine regulation of tTreg cell generation. By integrating the key findings of cytokines in tTreg cell generation, we have concluded that four members of γc family cytokines (IL-2, IL-4, IL-7 and IL-15), transforming growth factor β (TGF-β), and three members of TNF superfamily cytokines (GITRL, OX40L and TNF-α) play vitally important roles in regulating tTreg cell generation. We also point out all disputed points and highlight critical scientific questions that need to be addressed in the future.